Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Karyawan Pada PT. Panasea Banjarmasin - Kadir, Abdul; Melania, Melania; Jayen, Fredy; Syaukillah, Achmad (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2023)
This study aims to examine the effect of workload and work stress on employee performance at PT. Panasea Banjarmasin. The research approach used is a quantitative approach. This type of research is causal associative in nature, namely research that explains the influence between workload and work stress variables on employee performance variables at PT. Panasea Banjarmasin. The population in this study are employees of PT. Panasea Banjarmasin, totaling 37 people. The sampling technique used in this study was non-probability sampling using the saturated sampling method where all members of the population, totaling 37 employees, became members of the sample. Data were analyzed using Instrument Test, Classical Assumption Test, and Multiple Linear Regression. The results of this study indicate that workload and work stress have a significant simultaneous effect on employee performance at PT. Panasea Banjarmasin. Workload and work stress have a partially significant effect on employee performance at PT. Panasea Banjarmasin. Work stress is a variable that has a dominant influence on employee performance at PT. Panasea Banjarmasin.